The optimization of context-sensitive spelling correction process by simplification of calculation of semantic words closeness measure - Заболотня, Т. М. (Problems of Informatization and Control, 2007)
The choice of software resource, which it is expedient to use for determination of variants of the distorted word correction near on sense to the context of the last, is grounded. The approach to the calculation of measure of semantic accordance between set of correction hypothesis and surroundings of word with an error is offered. The efficiency of the dictionary resource traversal in direction from nodes which correspond the items of the distorted word context is shown